Assessment of Building Reliability in the Gedung Kuliah Bersama (GKB) of State Polytechnic Fakfak West Papua - Saisbuwono Bauw, Umas; Wibowo, Ari; Wijatmiko, Indradi (Universitas Ibn Khaldun Bogor, 2022)
The engineer must pay attention to strength, comfort, frugality, and impact on the environment in the building planning both in multi-storey or non-storey. Those aspects must be carefully planned and taken into a capable management system in it and to comply the comfort aspect in the building, hence disaster risk management such as fire prevention is needed. The purpose of this research is to evaluate the fire prevention and control system based on Minister of Public Works Regulation No.26/PRT/M/2008 and Indonesian National Standart 03-6574-2001, analyze the building reliability, and provide alternative solutions for the fire disaster control system in the college building of Fakfak State Polytechnic. The result of check list observation showed the average suitability was . The calculation result of Value of the Building Safety System Components using the Pd-T-11-2005-c guideline based on Analytical Hierarchy Process (AHP) was 64.23 % < 80%. It was classified into GOOD ENOUGH. From the results, alternative solution that can be proposed for college building at Fakfak State Polytechnic is to establish fire prevention.